Characterization of the Thermotolerant Cell. I. Effects on Protein Synthesis Activity and the Regulation of Heat-Shock Protein 70 Expression - Mizzen, Lee A.; Welch, William J. (The Journal of cell biology, 1988)
Exposure of mammalian cells to a nonlethal heat-shock treatment, followed by a recovery period at 37°C, results in increased cell survival after a subsequent and otherwise lethal heat-shock treatment. Here we characterize this phenomenon, termed acquired thermotolerance, at the level of translation. In a number of different mammalian cell lines given a severe 45°C/30-min shock and then returned to 37°C, protein synthesis was completely inhibited for as long as 5 h. Upon resumption of translational activity, there was a marked induction of heat-shock (or stress) protein synthesis, which continued for several hours. In contrast, cells first made thermotolerant (by a pretreatment consisting of a 43°C/1.5-h shock and further recovery at 37°C) and then presented with the 45°C/30-min shock exhibited considerably less translational inhibition and an overall reduction in the amount of subsequent stress protein synthesis. The acquisition and duration of such "translational tolerance" was correlated with the expression, accumulation, and relative half-lives of the major stress proteins of 72 and 73 kD. Other agents that induce the synthesis of the stress proteins, such as sodium arsenite, similarly resulted in the acquisition of translational tolerance. The probable role of the stress proteins in the acquisition of translational tolerance was further indicated by the inability of the amino acid analogue, L-azetidine 2-carboxylic acid, an inducer of nonfunctional stress proteins, to render cells translationally tolerant. If, however, analogue-treated cells were allowed to recover in normal medium, and hence produce functional stress proteins, full translational tolerance was observed. Finally, we present data indicating that the 72- and 73-kD stress proteins, in contrast to the other major stress proteins (of 110, 90, and 28 kD), are subject to strict regulation in the stressed cell. Quantitation of 72- and 73-kD synthesis after heat-shock treatment under a number of conditions revealed that "titration" of 72/73-kD synthesis in response to stress may represent a mechanism by which the cell monitors its local growth environment.